An automated in vitro motility assay for high-throughput studies of molecular motors. Issue 20 (11th September 2018) - Korten, Till; Tavkin, Elena; Scharrel, Lara; Kushwaha, Vandana Singh; Diez, Stefan
Abstract : Molecular motors, essential to force-generation and cargo transport within cells, are invaluable tools for powering nanobiotechnological lab-on-a-chip devices. Abstract : Molecular motors, essential to force-generation and cargo transport within cells, are invaluable tools for powering nanobiotechnological lab-on-a-chip devices. These devices are based on in vitro motility assays that reconstitute molecular transport with purified motor proteins, requiring a deep understanding of the biophysical properties of motor proteins and thorough optimization to enable motility under varying environmental conditions. Until now, these assays have been prepared manually, severely limiting throughput. To overcome this limitation, we developed an in vitro motility assay where sample preparation, imaging and data evaluation are fully automated, enabling the processing of a 384-well plate within less than three hours. We demonstrate the automated assay for the analysis of peptide inhibitors for kinesin-1 at a wide range of concentrations, revealing that the IAK domain responsible for kinesin-1 auto-inhibition is both necessary and sufficient to decrease the affinity of the motor protein for microtubules, an aspect that was hidden in previous experiments due to scarcity of data.